The diagnostic accuracy of ultrasonography over manual aspiration for gastric reserve volume estimation in critically ill patients - Rahul Sharma; Ravi Kant Dogra; Jyoti Pathania; Arti Sharma (Acute and Critical Care, 2023)
Background Although gastric reserve volume (GRV) is a surrogate marker of gastrointestinal dysfunction and feeding intolerance, there is ambiguity in its estimation due to problems associated with its measurement. Introduction of point-of-care ultrasound as a tool for anesthetists kindled interest in its use for GRV estimation. Methods In this prospective observational study, we recruited 57 critically ill patients and analyzed 586 samples of GRV obtained by both ultrasonography (USG) and manual aspiration. Results The analysis showed that USG-guided GRV was significantly correlated (r=0.788, P<0.001) and in positive agreement with manual aspiration based on Bland-Altman plot, with a mean difference of 8.50±14.84 (95% confidence interval, 7.389–9.798). The upper and lower limits of agreement were 37.7 and –20.5, respectively, within the ±1.96 standard deviation (P<0.001). The respective sensitivity and positive predictive value, specificity and negative predictive value, and area under the curve of USG for feeding intolerance were 66.67%, 98.15%, and 0.82%, with 96.49% diagnostic accuracy. Conclusions Ultrasonographic estimation of GRV was positively, significantly correlated and in agreement with the manual aspiration method and estimated feeding intolerance earlier. Routine use of gastric USG could avoid clinical situations where feeding status is unclear and there is high risk of aspiration and could become a standard practice of critical care.